Renewable resin-based adsorbent for air carbon capture and preparation method and application thereof
By combining weakly alkaline anionic resin with metal ions, an efficient resin-based adsorbent is prepared, which solves the problems of low adsorption capacity of existing adsorbents and large energy consumption, and achieves efficient CO2 adsorption and recycling, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202410727641.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-06
AI Technical Summary
The existing adsorbents used for direct air carbon capture have the disadvantages of low adsorption capacity and large energy consumption for regeneration, making it difficult to achieve industrial application, and the captured CO2 storage process requires a large amount of energy.
An adsorbent with high CO2 adsorption properties is prepared by mixing and stirring a weakly alkaline anionic resin with a metal ion solution to form a chelate, and then impregnating and drying in an alkaline solution. The adsorbent can be sealed by seawater washing, and regenerated by alkaline solution and recycled.
It achieves efficient CO2 adsorption and regeneration. The adsorption amount of adsorbent only decreases by 1% after 10 cycles, and the regeneration energy consumption is low, avoiding the attenuation of adsorption capacity caused by thermal regeneration. It is suitable for industrial applications.
Smart Images

Figure CN118384871B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of CO2 direct air carbon capture, and in particular to a renewable resin-based adsorbent for air carbon capture, and a preparation method and application thereof. Background Art
[0002] At present, a series of natural disasters caused by excessive global carbon emissions have become a major problem that the world urgently needs to solve, and CCUS (carbon capture, utilization and storage) technology has emerged. my country has also proposed dual carbon goals, but the current research focus is only on carbon capture at fixed locations such as some power plants and waste incineration plants that emit large amounts of CO2. Mobile source CO2 emissions generally refer to CO2 emissions generated by human daily activities and transportation, accounting for 40% of total emissions. They have the characteristics of small emission points, wide distribution, and large number. They are not easy to capture, resulting in low capture efficiency. At present, the adsorbents used for direct air carbon capture have the disadvantages of low adsorption capacity and high regeneration energy consumption, which makes it difficult to achieve industrial application. Moreover, the CO2 after carbon capture is mainly stored in the land and the ocean. This process requires a lot of energy to achieve. Therefore, finding a renewable adsorbent with low price, high adsorption capacity and easy storage of captured CO2 is an important way to develop air carbon capture. Summary of the invention
[0003] In view of the defects in the prior art, the present invention proposes a renewable resin-based adsorbent for air carbon capture and a preparation method and application thereof.
[0004] The present invention provides a method for preparing a resin-based adsorbent for air carbon capture, comprising the following steps:
[0005] S1: Modification: The resin material is mixed with the metal ion solution and stirred, and the metal ions are combined with the amine groups in the resin to form a stable chelate to obtain a base material loaded with metal ions;
[0006] S2: Immersing: Immerse the base material obtained in S1 in an alkaline solution and stir. The OH in the alkaline solution - Combined with chelate to obtain modified resin material;
[0007] S3: Drying: Drying the resin material obtained in S2 to remove excess water to obtain a resin-based adsorbent for air carbon capture;
[0008] Wherein, the resin material is a weakly basic anion resin, that is, a resin with amine groups, which provide binding sites for metal ions. The amine content of the weakly basic anion resin is 7.0-10.0 mmol / g, and the resin type is styrene polyamine type (WA20, D301, etc.) and acrylic polyamine type (D941, etc.). The metal ion solution in step S1 is an iron-based transition metal with strong electron receiving ability (complexation ability), including but not limited to one or more of ferric sulfate, ferric chloride, nickel nitrate, nickel chloride, cobalt sulfate, and cobalt chloride solution;
[0009] A low amine group density of weakly alkaline anion resin is not conducive to the immobilization of metal ions, resulting in poor CO2 capture performance; a high amine group content will cause the amine group to form a multi-component complex with the metal ion, reducing the ability of the metal ion to bind to hydroxide and resulting in a decrease in adsorption capacity. In addition, a high amine group density will also increase the cost of the resin.
[0010] The metal ions are loaded onto the resin by the stirring and impregnation method. The metal ions chelate with the amine groups in the weakly alkaline anion resin, and the combination is stable and not easy to come out. The prepared modified resin-based adsorbent has high CO2 adsorption performance.
[0011] Furthermore, in step S1, the molar ratio of the amine group to the metal ion is (1-3):1, which can ensure the stability of the combination of the metal ion and the resin. Preferably, the molar ratio of the amine group to the metal ion is (2-3):1.
[0012] Furthermore, the alkaline solution in step S2 is one or more of sodium hydroxide, calcium hydroxide, potassium hydroxide, and barium hydroxide solution, and the mass concentration of the alkaline solution is 0.1-2%, preferably 0.5-1%.
[0013] Furthermore, the pH value of the alkaline solution is in the range of 10-14, ensuring that OH - The preferred pH range is 11-13 to smoothly combine with the chelate without damaging the base material due to excessive concentration.
[0014] Furthermore, the concentration of the metal ion solution in step S1 is 0.05-5 g / L, preferably 1-3 g / L. A higher ion concentration increases the amount and speed of loaded metal ions.
[0015] Furthermore, the mixing and stirring time in step S1 is 0.5-5 h, the stirring speed is 50-500 r / min, the stirring temperature is 25-65° C., and the immersion and stirring time in the alkaline solution in step S2 is 0.5-5 h.
[0016] Furthermore, in step S3, the drying time is 5-20 h, and the drying temperature is 40-100°C.
[0017] The present invention also provides a CO2 adsorbent prepared according to the method.
[0018] The present invention also provides the use of the adsorbent in adsorbing CO2 in the air or in cyclic regeneration;
[0019] The adsorption temperature of the adsorbent is 0℃-60℃, the airflow is a CO2 airflow with a concentration of 400-2000 ppm and a relative humidity of 0%-90%. During the adsorption process, CO2 first reacts with water vapor to generate HCO3 - , and then react with the hydroxyl group bound to the chelate in the adsorbent to achieve the adsorption of CO2.
[0020] The present invention also provides a regeneration method for the use of the adsorbent in cyclic regeneration, comprising the following steps:
[0021] The seawater reacts with the adsorbent after adsorption, and after the reaction is completed, an alkaline solution equal to the seawater is added to complete the regeneration of the adsorbent;
[0022] The adsorbent is made to react with seawater after adsorption. The adsorbent passes through the seawater in the fixed bed (the volume of seawater is 50-60 times that of the adsorbent). - Replace HCO3 - , the adsorbed CO2 is directly stored in the ocean to achieve CO2 storage, and OH is supplemented by alkaline solution - After that, the adsorbent can be regenerated (the volume of the alkaline solution used is equal to that of seawater) to achieve the recycling of the adsorbent. When the adsorbent passes through seawater, it reacts with the sodium chloride in the seawater to generate sodium bicarbonate, and the captured CO2 is directly stored in the ocean. Compared with traditional storage technology, this step saves a lot of manpower and resources, reduces the cost of transportation and storage, and the adsorbent can store CO2 after passing through seawater, and then obtains OH from a mixed solution of one or more of sodium hydroxide, calcium hydroxide, potassium hydroxide, and barium hydroxide solutions. - Regeneration is achieved and it can be used for the next adsorption.
[0023] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0024] (1) The present application provides a method for preparing an adsorbent with simple preparation steps and easy sample preparation.
[0025] (2) After the adsorption material prepared by the present invention is saturated with adsorption, it can be washed with seawater to achieve CO2 storage. The adsorbent can be regenerated by simple alkaline solution treatment. The regeneration energy consumption is low and the adsorption capacity attenuation caused by thermal regeneration is avoided.
[0026] (3) The present application provides an air carbon capture adsorbent with high adsorption performance, which has a high adsorption capacity in a low concentration CO2 adsorption atmosphere of 400-2000 ppm.
[0027] (4) The present application provides a regenerable air carbon capture adsorbent. The regenerated adsorbent can be used for cyclic adsorption and has good stability. After 10 cycles, the adsorption amount only decreased by 1%. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a preparation process diagram of the resin-based adsorbent of the present invention.
[0029] Figure 2 It is a single penetration adsorption graph of the resin-based adsorbent loaded with metal ions and not loaded with metal ions in Example 1.
[0030] Figure 3 This is an infrared image of the resin-based adsorbent WA20 without metal ion loading in Example 1 of the present invention.
[0031] Figure 4 1 is an adsorption performance diagram of the resin-based adsorbent in Example 1 of the present invention after 10 cycles in a 400 ppm CO2 adsorption atmosphere. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0033] Example
[0034] 1. Adsorbent performance test
[0035] (1) Adsorption capacity test: The fixed bed adsorption setting procedure is as follows: First, the sample is adsorbed at 100 mL min -1 The sample was pretreated in a pure argon atmosphere. The sample temperature was raised to a specific temperature (100-150°C) and maintained for a certain period of time (30-90 min) to remove water, CO2 and other impurities in the adsorbent. Then the temperature was lowered to a specific adsorption temperature (25-55°C) and the carrier gas was immediately switched to 100 mL min-1 The concentration of CO2 is 400 ppm and has a certain relative humidity (0%-90%), and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography.
[0036] (2) Cycle number test: The adsorption procedure was basically the same as that of single adsorption, but the carrier gas flow rate was changed to 200 mL min -1 A CO2 atmosphere with a concentration of 400 ppm and a certain relative humidity (0%-90%) is used to complete the adsorption more quickly. During the desorption stage, the adsorbent is passed through seawater and an alkaline aqueous solution in turn. When the adsorption amount is less than 50%, it means that the number of cycles has reached saturation.
[0037] The preparation method of the adsorbent of the embodiment and the comparative example of the present invention comprises the following steps:
[0038] Modification: Add a certain amount of weakly alkaline anion resin material to the metal ion solution, place it in a magnetic stirrer and stir it at a speed of 50-500 r / min for 0.5-5 h. After stirring, wash the material with deionized water to rinse off the excess metal ions;
[0039] Impregnation: Immerse the cleaned resin material in an alkaline solution for 0.5-5 h and stir. Rinse the impregnated material with deionized water to remove excess OH - flush out;
[0040] Drying: Place the cleaned sample in a vacuum drying oven for 5-20 h at a temperature of 40-100°C;
[0041] Adsorption: The resin-based adsorbent prepared above is passed through a fixed bed, and suitable test conditions are selected according to the properties of the sample for single adsorption and multiple cycles, and the adsorption amount is compared with the resin material not modified with metal ions;
[0042] Regeneration: The adsorbent after adsorption can be washed with 50-60 times the volume of seawater, and then soaked in an alkaline solution equal to the amount of seawater to obtain a regenerated adsorbent, which can be used for the next adsorption.
[0043] The drugs used in the present invention are all commercially available, and the solutions are all prepared according to experimental needs.
[0044] Example 1
[0045] Step 1. Weigh 2 g of weakly basic anion resin WA20, add 300 mL of ferric chloride solution, the molar ratio of amine group to iron ion is 3:1, stir at 300 r / min at room temperature for 3 h, wash the resin after loading metal ions with deionized water, and obtain a modified WA20 resin with a molar ratio of amine group to iron ion of 3:1;
[0046] Step 2: Immerse the cleaned resin in a 1% sodium hydroxide solution and stir for 2 h. The pH of the sodium hydroxide solution is 13. After the immersion is completed, use deionized water to wash away the excess OH. - ;
[0047] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 50°C for 10 h. The dried sample is the metal ion-modified resin material that can be used for direct air carbon capture.
[0048] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1 The sample temperature was raised to 100 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 CO2 with a concentration of 400 ppm and a relative humidity of 50%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0049] Step 5. Immerse the saturated adsorbent in seawater solution and stir for 1 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1 h. After the immersion is completed, wash away the excess OH with deionized water. - , the adsorbent can be regenerated and can be used for the next adsorption.
[0050] Figure 2 This is a single penetration adsorption diagram of the resin-based adsorbent loaded with metal ions and unloaded with metal ions in Example 1. The loaded metal ions are iron ions, the adsorption temperature is 25°C, the adsorption atmosphere is 50% relative humidity and the CO2 concentration is 400ppm. The adsorption capacity of the adsorbent modified with metal ions can reach 6.0 mmol·g 吸附剂 -1 The adsorption capacity of the unmodified adsorbent is only 2.5 mmol·g 吸附剂 -1 ; Figure 3 This is the infrared image of the resin-based adsorbent WA20 without metal ion loading in Example 1. It can be seen that the peaks at 1455 and 1581 cm -1 The characteristic peaks of amine groups appeared at the positions. These amine groups can combine with metal ions to form stable chelates, thus ensuring the stability of the adsorbent. Figure 4 This is the adsorption performance diagram of the resin-based adsorbent in Example 1 after 10 cycles in a 400 ppm CO2 adsorption atmosphere. After 10 cycles, the adsorption amount only decreased by 1%, and still maintained a good adsorption performance.
[0051] Example 2
[0052] Step 1. Weigh 2 g of weakly basic anion resin WA20, add 300 mL of ferric chloride solution, stir at 300 r / min for 3 h at room temperature, wash the resin after loading metal ions with deionized water, and obtain a modified WA20 resin with a molar ratio of amine group to iron ion of 3:1;
[0053] Step 2: Immerse the cleaned resin in a 1% sodium hydroxide solution and stir for 2 h. The pH of the sodium hydroxide solution is 12. After the immersion is completed, use deionized water to wash away the excess OH. - ;
[0054] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 50°C for 10 h. The dried sample is the metal ion-modified resin material that can be used for direct air carbon capture.
[0055] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration performance test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1 The sample temperature was raised to 100 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 CO2 with a concentration of 400 ppm and a relative humidity of 50%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0056] Step 5. Immerse the saturated adsorbent in seawater solution and stir for 1 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1 h. After the immersion is completed, wash away the excess OH with deionized water. - , the adsorbent can be regenerated and can be used for the next adsorption.
[0057] Example 3
[0058] Step 1. Weigh 2 g of weakly basic anion resin WA20, add 300 mL of ferric chloride solution, stir at 300 r / min for 3 h at room temperature, wash the resin after loading metal ions with deionized water, and obtain a modified WA20 resin with a molar ratio of amine group to iron ion of 3:1;
[0059] Step 2: Immerse the cleaned resin in a 0.1% sodium hydroxide solution and stir for 2 h. The pH of the sodium hydroxide solution is 11. After the immersion is completed, use deionized water to wash away the excess OH.- ;
[0060] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 50°C for 10 h. The dried sample is the metal ion-modified resin material that can be used for direct air carbon capture.
[0061] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1 The sample temperature was raised to 100 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 CO2 with a concentration of 400 ppm and a relative humidity of 50%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0062] Step 5. Immerse the saturated adsorbent in seawater solution and stir for 1 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1 h. After the immersion is completed, wash away the excess OH with deionized water. - , the adsorbent can be regenerated and can be used for the next adsorption.
[0063] Example 4
[0064] Step 1. Weigh 2 g of weakly basic anion resin WA20, add 300 mL of ferric chloride solution, stir at 300 r / min for 3 h at room temperature, wash the resin after loading metal ions with deionized water, and obtain a modified WA20 resin with a molar ratio of amine group to iron ion of 3:1;
[0065] Step 2: Immerse the cleaned resin in a 1% sodium hydroxide solution and stir for 2 h. The pH of the sodium hydroxide solution is 14. After the immersion is completed, use deionized water to wash away the excess OH. - ;
[0066] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 50°C for 10 h. The dried sample is the metal ion-modified resin material that can be used for direct air carbon capture.
[0067] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1The sample temperature was raised to 100 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 The concentration of CO2 is 400 ppm and the relative humidity is 50%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0068] Step 5. Immerse the saturated adsorbent in seawater solution and stir for 1 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1 h. After the immersion is completed, wash away the excess OH with deionized water. - , the adsorbent can be regenerated and can be used for the next adsorption.
[0069] Example 5
[0070] Step 1. Weigh 2 g of weakly basic anion resin D301, add 300 mL of ferric chloride solution, stir at 300 r / min for 3 h at room temperature, wash the resin after loading metal ions with deionized water, and obtain a modified D301 resin with a molar ratio of amine group to iron ion of 3:1;
[0071] Step 2. Immerse the cleaned resin in a 1% calcium hydroxide solution and stir for 2 h. The pH of the sodium hydroxide solution is 13. After the immersion is completed, use deionized water to wash away the excess OH. - ;
[0072] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 50°C for 10 h. The dried sample is the metal ion-modified resin material that can be used for direct air carbon capture.
[0073] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1 The sample temperature was raised to 120 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 CO2 with a concentration of 400 ppm and a relative humidity of 50%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0074] Step 5. Immerse the saturated adsorbent in seawater solution and stir for 1 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1 h. After the immersion is completed, wash away the excess OH with deionized water. -, the adsorbent can be regenerated and can be used for the next adsorption.
[0075] Example 6
[0076] Step 1. Weigh 2 g of weakly basic anion resin D301, add 300 mL of nickel chloride solution, stir at 300 r / min for 3 h at room temperature, wash the resin after loading metal ions with deionized water, and obtain a modified D301 resin with a molar ratio of amine group to nickel ion of 3:1;
[0077] Step 2: Immerse the cleaned resin in a 1% sodium hydroxide solution and stir for 2 h. The pH of the sodium hydroxide solution is 13. After the immersion is completed, use deionized water to wash away the excess OH. - ;
[0078] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 50°C for 10 h. The dried sample is the metal ion-modified resin material that can be used for direct air carbon capture.
[0079] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1 The sample temperature was raised to 120 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 CO2 with a concentration of 400 ppm and a relative humidity of 50%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0080] Step 5. Immerse the saturated adsorbent in seawater solution and stir for 1 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1 h. After the immersion is completed, wash away the excess OH with deionized water. - , the adsorbent can be regenerated and can be used for the next adsorption.
[0081] Example 7
[0082] Step 1. Weigh 2.0 g of weakly basic anion resin WA20, add 300 mL of ferric chloride solution, stir at 40 ° C and 50 r / min for 0.5 h, wash the resin after loading metal ions with deionized water to obtain a modified WA20 resin with a molar ratio of amine group to iron ion of 1:1;
[0083] Step 2: Immerse the cleaned resin in a 0.1% sodium hydroxide solution and stir for 0.5h. The pH of the sodium hydroxide solution is 11. After the immersion is completed, use deionized water to wash away the excess OH. - ;
[0084] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 80°C for 5 h. The dried sample is the resin material modified with metal ions and can be used for direct air carbon capture.
[0085] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration performance test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1 The sample temperature was raised to 120 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 0 °C and the carrier gas was immediately switched to 100 mL min -1 The concentration of CO2 is 1000 ppm, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0086] Step 5. Immerse the saturated adsorbent in seawater solution and stir for 0.5 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1.5 h. After the immersion is completed, wash away the excess OH with deionized water. - , the adsorbent can be regenerated and can be used for the next adsorption.
[0087] Example 8
[0088] Step 1. Weigh 2.0 g of weakly basic anion resin WA20, add 300 mL of cobalt chloride solution, stir at 65°C and 500 r / min for 5 h, wash the resin after loading metal ions with deionized water to obtain a modified WA20 resin with a molar ratio of amine group to cobalt ion of 1:1;
[0089] Step 2: Immerse the cleaned resin in a 2% sodium hydroxide solution and stir for 5 hours. The pH of the sodium hydroxide solution is 14. After the immersion is completed, use deionized water to wash away the excess OH. - ;
[0090] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 100°C for 15 h. The dried sample is the metal ion-modified resin material that can be used for direct air carbon capture.
[0091] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration performance test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1The sample temperature was raised to 120 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 60 °C and the carrier gas was immediately switched to 100 mL min -1 CO2 with a concentration of 2000 ppm and a relative humidity of 90%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0092] Step 5. Immerse the saturated adsorbent in seawater solution and stir for 0.5 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1.5 h. After the immersion is completed, wash away the excess OH with deionized water. - , the adsorbent can be regenerated and can be used for the next adsorption.
[0093] Comparative Example 1
[0094] Step 1. Weigh 2 g of weakly alkaline anion resin WA20, immerse it in a 1% sodium hydroxide solution and stir for 2 h. The pH of the sodium hydroxide solution is 13. After the immersion is completed, wash off the excess OH with deionized water. - ;
[0095] Step 2. Place the treated resin in a vacuum drying oven and vacuum dry it at 50 °C for 10 h;
[0096] Step 3. The adsorbent prepared above was subjected to a fixed bed penetration test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1 The sample temperature was raised to 100 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 CO2 with a concentration of 400 ppm and a relative humidity of 50%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0097] Step 4. Immerse the saturated adsorbent in seawater solution and stir for 1 h, then immerse it in 0.5% sodium hydroxide solution and stir for 1 h. After the immersion is completed, wash away the excess OH with deionized water. - .
[0098] Comparative Example 2
[0099] Step 1. Weigh 2 g of weakly basic anion resin WA20, add 300 mL of ferric chloride solution, stir at 300 r / min for 3 h at room temperature, wash the resin after loading metal ions with deionized water, and obtain a modified WA20 resin with a molar ratio of amine group to iron ion of 3:1;
[0100] Step 2. Place the treated resin in a vacuum drying oven and vacuum dry it at 50 °C for 10 h. The dried sample is used for direct air carbon capture;
[0101] Step 3. The adsorbent prepared above was subjected to a fixed bed penetration test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1 The sample temperature was raised to 100 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 The concentration of CO2 is 400 ppm and the relative humidity is 50%, and the concentration of the gas passing through the adsorbent at the outlet is detected by gas chromatography;
[0102] Step 4. Immerse the adsorbent after adsorption saturation in seawater solution and stir for 1 h, then immerse it in a 0.5% sodium hydroxide solution for 1 h. After immersion, wash away the excess OH with deionized water. - , the adsorbent can be regenerated and can be used for the next adsorption.
[0103] Comparative Example 3
[0104] Step 1. Weigh 2 g of weakly basic anion resin WA20, add 300 mL of copper sulfate solution, stir at 300 r / min for 3 h at room temperature, wash the resin after loading metal ions with deionized water, and obtain a modified WA20 resin with a molar ratio of amine group to copper ion of 3:1;
[0105] Step 2: Immerse the cleaned resin in a 1% sodium hydroxide solution and stir for 2 h. The pH of the sodium hydroxide solution is 13. After the immersion is completed, use deionized water to wash away the excess OH. - ;
[0106] Step 3. Place the treated resin in a vacuum drying oven and vacuum dry it at 50°C for 10 h. The dried sample is the metal ion-modified resin material that can be used for direct air carbon capture.
[0107] Step 4. The adsorbent prepared above was subjected to a fixed bed penetration performance test. 0.5 g of sample was taken and stirred in pure argon gas at 100 mL min -1The sample temperature was raised to 100 °C and maintained for 30 min to remove water, CO2 and other impurities in the adsorbent. The sample was then cooled to a specific adsorption temperature of 25 °C and the carrier gas was immediately switched to 100 mL min -1 The concentration of CO2 was 400 ppm and the relative humidity was 50%, and the concentration of the gas at the outlet of the adsorbent was detected by gas chromatography.
[0108] Table 1 Performance test results of examples and comparative examples
[0109]
[0110] Table 1 Performance test results of the examples and comparative examples
[0111]
[0112] Table 2 Cyclic test results of Example 1
[0113]
[0114] Comparative Examples 1-3 are all compared with Example 1 by a single variable. In Comparative Example 1, the weakly basic anion resin is not modified by a metal ion solution, so that the adsorbent can only rely on amine adsorption, and the adsorption amount is low; and in Comparative Example 2, the weakly basic anion resin modified by metal ions is not immersed in an alkaline solution, resulting in the chelate not being bound to the hydroxyl group, and the adsorption capacity is greatly reduced; the metal ion solution used in Comparative Example 3 is copper sulfate, and the adsorbent prepared has a lower adsorption capacity than that of Example 1.
[0115] Based on Table 1-2 and Figure 1-4 The data of the adsorption capacity and cycle test of the adsorbent show that the adsorbent prepared by Examples 1-8 can be regenerated while ensuring a high adsorption capacity, and the material can continue to maintain good adsorption performance, and the adsorption capacity can reach 5.1 mmol·g 吸附剂 -1 And above, compared with the comparative example, it has obvious advantages, and the adsorbent production process is simple and low-cost, which can effectively meet the high-standard demands of customers and the market.
[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a resin-based adsorbent for air carbon capture, characterized in that: The invention comprises the following steps: S1: modification: mixing and stirring a resin material with a metal ion solution to obtain a base material loaded with metal ions; S2: impregnation: immersing the base material obtained in S1 in an alkaline solution and stirring to obtain a modified resin material; S3: drying: drying the resin material obtained in S2 to obtain a resin-based adsorbent for air carbon capture; wherein the resin material is a weakly alkaline anion resin; the metal ions in step S1 are iron ions; the amine content of the weakly alkaline anion resin is 7.0-10.0 mmol / g, and the type of the weakly alkaline anion resin is a styrene polyamine type and an acrylic polyamine type; the molar ratio of amine to metal ion in step S1 is (1-3): 1; the alkaline solution in step S2 is one or more of sodium hydroxide, calcium hydroxide, potassium hydroxide, and barium hydroxide solution, and the mass concentration of the alkaline solution is 0.1-2%; the pH value range of the alkaline solution in step S2 is 10-14.
2. The preparation method according to claim 1, characterized in that: The mixing and stirring time in step S1 is 0.5-5 h, the stirring speed is 50-500 r / min, and the stirring temperature is 25-65° C. The immersion and stirring time in the alkaline solution in step S2 is 0.5-5 h.
3. The preparation method according to claim 1, characterized in that: In step S3, the drying time is 5-20 h and the drying temperature is 40-100°C.
4. The adsorbent prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the adsorbent as claimed in claim 4 for adsorbing CO2 in the air.
6. A method for recycling an adsorbent as claimed in claim 4, characterized in that: The steps include: seawater reacts with the adsorbent after adsorption, and OH is added after the reaction is completed. - , that is, the regeneration of the adsorbent is completed.
Citation Information
Patent Citations
Direct air trapping carbon absorption material for desorption of salt solution and preparation and application of direct air trapping carbon absorption material
CN118022692A